2015
DOI: 10.1371/journal.pone.0144657
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of First Zoeal Stage of Four Genera of Alvinocaridid Shrimps from Hydrothermal Vents and Cold Seeps: Implications for Ecology, Larval Biology and Phylogeny

Abstract: Alvinocaridid shrimps are endemic species inhabiting hydrothermal vents and/or cold seeps. Although indirect evidences (genetic and lipid markers) suggest that their larval stages disperse widely and support large scale connectivity, larval life and mechanisms underlying dispersal are unknown in alvinocaridids. Here we provide for the first time detailed descriptions of the first larval stage (zoea I) of four alvinocaridid species: Rimicaris exoculata and Mirocaris fortunata from the Mid-Atlantic Ridge, Alvino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 67 publications
(114 reference statements)
0
26
0
Order By: Relevance
“…To date, no bacteria have been observed inside eggs of R. exoculata, but Gammaproteobacteria and Campylobacteria have been reported on their surface (Guri et al 2012, Cowart et al 2017, Methou et al 2019). In the same way, bacterial symbionts appear to be absent in the branchial chamber of post-hatching larvae of R. exoculata (Guri et al 2012, Hernandez-Avila et al 2015 or in their first juvenile stages after recruitment (Komai & Segonzac 2008). Some Campylobacteria and Gammaproteobacteria sequences retrieved from Rainbow seawater samples were closely related (99% similarity) to epibiont sequences from the branchial chamber of shrimp from the same site (Guri et al 2012).…”
Section: Branchial Chamber Symbiontsmentioning
confidence: 80%
See 4 more Smart Citations
“…To date, no bacteria have been observed inside eggs of R. exoculata, but Gammaproteobacteria and Campylobacteria have been reported on their surface (Guri et al 2012, Cowart et al 2017, Methou et al 2019). In the same way, bacterial symbionts appear to be absent in the branchial chamber of post-hatching larvae of R. exoculata (Guri et al 2012, Hernandez-Avila et al 2015 or in their first juvenile stages after recruitment (Komai & Segonzac 2008). Some Campylobacteria and Gammaproteobacteria sequences retrieved from Rainbow seawater samples were closely related (99% similarity) to epibiont sequences from the branchial chamber of shrimp from the same site (Guri et al 2012).…”
Section: Branchial Chamber Symbiontsmentioning
confidence: 80%
“…For example, Vereshchaka et al (1998) noted that R. exoculata is represented in Russian collections by thousands of individuals, among which brooding females are absent. This absence was linked to seasonal breeding and sampling efforts almost entirely restricted to the summer months (Gebruk et al 1997a, Herring 1998, Vereshchaka et al 1998, Ramirez-Llodra et al 2000, Guri et al 2012, Hernandez-Avila et al 2015, Hernandez-Avila 2016. It was also suggested that ovigerous R. exoculata leave the aggregations around high temperature vents, where samples are generally collected, to protect the embryos from hydrothermal fluids and from the risk of mechanical damage caused by the highly active shrimp aggregations (Ramirez-Llodra et al 2000).…”
Section: Brooding and Fecunditymentioning
confidence: 99%
See 3 more Smart Citations